“Respuesta de tres niveles de fertilización nitrogenada y tres densidades de siembra sobre el rendimiento del cultivo maíz (zea mays)-hibrido pimse 3, bajo riego; en la estación experimental el porvenir-tarapoto” - Tello Rodriguez, Miguel Angel (2002)
The present res.earch took place at the experimental station of the "El Porvenir", located in 14,5 km of the Marginal Sur Road, Juan Guerra, District, Province of San Martin (Perú), located al 6º 35'south latitude, at 232 above sea level, a~d 76º 30' longitude. Our aim was to find and the best nitrogen dose and an adecuate seed planting density far hybrid corn - type PIMSE 3. The results were evaluated in three levels nitrogen fertilizing and there different seed - planting density related to harvest efficiency in the Bajo Mayo river area. The nitrogen dose was 120, 150 and 180 kg por hectare and the seed - planting density was 50 000, 62 500 and 70 ooo. plants por hectare, using nitrogen in two times: first time, 1 O days after seed planting, and the second time at the present harvest. We used the experimental design of Divided lost or Parcels of Ground divided in four areas analyzing 9 different treatments with 36 experimental units, and the results were verified using an analysis of changing and the Duncan Multiple Range test. The soil where the experiment tool place, had a regular percentage of organic materia and high argillaceous texture. From the results we can conclude that the treatment T9 (180 N - 70 000 plant far hectare) reached the maximum efficiency of 5 225 plants/hectare, in comparison with the treatment T3 (120 N - 70 000 plants/hectare) which obtain less efficiency: 4 343 kg/hectare. As a result of the economic analysis, we can say that the T1 treatment (120 N - 50 000 plants/hectare), occupied the third place in efficiency with 4 868 kg/Ha, so this is the treatment which show the best economic efficiency, that is to say the treatment which obtained the best economic profits.